Utilization of Polyurethane with Bentonite-Chitosan Filler As an Anti-Corrosion Paint - Izzati, Isra Adelya; Rihayat, Teuku; Putra, Alfian (Jurnal Sains dan Teknologi Reaksi, 2024)
ABSTRACTIn this study, the manufacture of polyurethane uses bentonite-chitosan filler materials to improve the ability of heat resistance. The characteristics carried out were assessed in terms of functional group analysis, heat resistance analysis, morphological structure analysis, corrosion test and paint thickness test. The coating process has the advantage of being able to protect the iron surface from environmental influences that result in corrosion of the metal. This study aims to see the effect of mixing polyurethane with Bentonite-Chitosan filler. The sample formulation used was polyurethane with variations of bentonite and chitosan of 2%, 4%, 6%, 8%. The results of the Fourier Transform Infra Red (FT-IR) test showed that there were functional groups N-H, C-H, C=O. Based on the results of the Thermogravimetry Analysis (TGA) test, the Polyurethane sample with 8% bentonite modification : chitosan 8% b/b had the best thermal stability among other samples where the sample began to degrade (on set) at a temperature of 307.04 (oC) and stopped degrading (end set) at a temperature of 399.50 (oC). In the Polyurethane sample with 2% bentonite modification/8% chitosan b/b had lower thermal stability where the sample began to degrade (onset) 293.09(oC) and stopped degrading (end set) at 348.32(oC). The results of the morphological test using SEM tools showed that the chitosan chain was well dispersed into the bentonite interlayer. The corrosion test showed that the addition of bentonite and chitosan affected the corrosion rate, the greater the composition of bentonite and chitosan, which could reduce the corrosion rate. The best sample with a ratio of Polyurethane/Bentonite/Chitosan 8:8 % b/b experienced the smallest corrosion rate of 5.79 mpy and mass loss of 0.10 grams.Keywords : Biodegradable, Corrosion, Polyurethane, Bentonite, Chitosan